Site formation processes of submerged shipwrecks - Keith, Matthew E. (Co-published with The Society for Historical Archaeology., 2016)
Matthew Keith and the contributors to this volume provide a series of studies that examine the ways to identify the natural and anthropogenic processes that shape shipwreck site formation. The volume also showcases emerging technologies and methods by which archaeologists study shipwreck sites, including computer modeling and site reconstruction, as well as how human activities such as trawl fishing affect shipwreck sites.